Evaluation of the nutritional status and care of pregnant women in the Allada-Toffo Zè health zone (Benin) - GBANKOTO, Mamatou; POSSOU, Fifamè Fortunée Clémence; DEGNON, Gnimabou René; KPATINVOH, Brice Toyidè Dieu-Grand (My University, 2023)
This work aims to assess the nutritional status of pregnant women in the health zone of Allada-Toffo-Zè. It consisted of conducting an interview with pregnant women meeting the criteria of pregnant women and coming for prenatal consultation. During this study, 200 pregnant women were surveyed in health facilities in the health zone. The results showed that 80% of pregnant women have never received nutritional advice, which leads them to not control their diet. In addition, there is a relationship between the malnutrition of pregnant women and the age of pregnant women, and their profession. Indeed, pregnant women aged over 30 years are 1.85 times more malnourished than pregnant women under 20 years of age (p=0.007). Also, resellers or shopkeepers are 1.49 times more malnourished than housewives (p=0.001). Finally, weight and MUAC were associated with malnutrition in pregnant women. Therefore, pregnant women weighing more than 55 kg were malnourished than pregnant women weighing less than 55 kg (p=0.01). Those whose MUAC greater than 24 cm were malnourished (p=0.003).
Keywords: Nutritional status; Women; Pregnant; Consultation